Implementation of Regional Development Planning Policies at the Regional Development Planning Agency of Central Sulawesi Province: Study on the Preparation of the 2024 Central Sulawesi Provincial Government Work Plan - Steven Sukarno, Moh.; Riadi, Slamet; Kurnia, Intam (PT. Multidisciplinary Press Indonesia, 2024)
The aim to be achieved in this research is to obtain an overview of the Implementation of Regional Development Planning Policies at the Regional Development Planning Agency of Central Sulawesi Province (Study of the Preparation of the Regional Government Work Plan for Central Sulawesi Province in 2024). This type of research is descriptive, with a total of 5 informants, whose determination uses purposive techniques. Apart from that, the data collection techniques in this research were through observation, interviews and documentation. With a data analysis method with three steps, namely data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). Based on the results of research using Edward III's theory which has been discussed, the implementation of regional development planning policies at the Regional Development Planning Agency of Central Sulawesi Province (Study on the Preparation of Regional Government Work Plans for Central Sulawesi Province in 2024) has not been implemented well. This is due to the number of competent planning apparatus is still limited, community participation is still low, public consultations are not carried out and there are obstacles in the fragmentation aspect, namely adjustments to the sipd-ri application which results in the time at several stages not being in accordance with the schedule for preparing the 2024 RKPD.